Terapi Realita dalam bingkai Konseling sebagai Proses Penyesuaian Diri Santri di Ponpes Roudlotul Mustofa Al Banjari, Amuntai Kalimantan Selatan - Syafiq, Mohamad; Taufikkurahman, Taufikkurahman (Quanta : Jurnal Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
The background of this research is about the case of students at the Roudlotul Mustofa Al Banjari Islamic Boarding School who feel uncomfortable due to several tasks both at the boarding school and at school, generally unable to manage their time, which affects their life at the Islamic boarding school. Focus research on the reality therapy process for students' self-adjustment process and the results of reality therapy for students' self-adjustment process at the Roudlotul Mustofa Al Banjari Amuntai Islamic boarding school, South Kalimantan. Qualitative research method, with a descriptive approach and case study research type. Data collection techniques; observation, interviews and documentation. Data analysis uses descriptive analysis techniques, namely by describing the process of reality therapy counseling services and the results comparing the students' feelings before therapy and after receiving therapy services at the Islamic boarding school. Research results 1) The reality therapy process for the students' self-adjustment process at the Roudlotul Mustofa Al Banjari Amuntai Islamic Boarding School, South Kalimantan is the first stage by identifying the problem, then the second stage is carrying out therapy and the last stage or third stage is the evaluation stage where we evaluate about whether the desired things are in accordance with what the consli has done. 2) The results of reality therapy for students' self-adjustment at the Roudlotul Mustofa Al Banjari Amuntai Islamic Boarding School, South Kalimantan were successful, seeing that the condition of the students was better than before.